Strand 4: Networked Learning in Community Development and Economic Regeneration - Banks, Sheena; McConnell, David; Graebner, Celia (Proceedings of the International Conference on Networked Learning, 1998)
This Strand is concerned with how networked lifelong learning can increase access and broaden participation in lifelong learning for the wider community - for learners wherever they are. Examples in this Strand address good practice both in UK and international contexts. Papers discuss fundamental issues around the potential of ICT to improve access to lifelong learning: how technology can be provided for the wider community in cost-effective and sustainable forms, how the needs of lifelong learners can be met in the provision and design of ICT for lifelong learning. What type of technology is appropriate for lifelong learning and how can ICT literacy tools be developed which enable lifelong learners to perceive their benefits and effectively use them. The NIACE paper has investigated a number of case studies to identify relevant approaches co raising individual awareness of ICT. The Internet Express initiative in Merseyside describes how mobile internet facilities have contributed to the widespread availability of technology.